CARDIOVASCULAR SYSTEM INDICATORS IN THE PRIMARY SCHOOL-AGED CHILDREN DURING THE ADAPTATION TO EDUCATIONAL LOADS IN THE REGION WITH IODINE EFICIENCY - Yurchyshyn, O.M.; Komissarova, O.S.; Fartushok, T.V.; Palytsia, L.M.; Lokai, B.A. (World of Medicine and Biology, 2020)
The purpose of the study was to study the adaptive capacity of the cardiovascular system and to identify changes in the performance of heart rate variability in the primary school-aged children with iodine deficiency during the school year. It was found that among the 1st grade schoolchildren with iodine deficiency, 30% of children had the adaptive strategy tension at the beginning of the school year. The largest share of schoolchildren with low adaption level at the beginning of the school year was revealed. According to the indicators of heart rate variability, in 1-4 grades students with iodine deficiency the sympathetic nervous system influence is prevalent during the school year, while the parasympathetic nervous system is predominant in schoolchildren, properly provided with iodine.